Запорізький край на початку 20-х рр. ХХ ст.: адміністративні та соціально-політичні зміни. (Zaporizhzhia Historical Review, 2021)
The basic changes of administrative and sociopolitical character which has occurred in the territory of Zaporizhzhya region in connection with the statement of the Bolsheviks power in the beginning of 20th ХХ century was characterized by author.